2023
DOI: 10.1111/1475-6773.14175
|View full text |Cite
|
Sign up to set email alerts
|

Advancing healthcare equity through dissemination and implementation science

Abstract: ObjectiveTo provide guiding principles and recommendations for how approaches from the field of dissemination and implementation (D&I) science can advance healthcare equity.Data Sources and Study SettingThis article, part of a special issue sponsored by the Agency for Healthcare Research and Quality (AHRQ), is based on an outline drafted to support proceedings of the 2022 AHRQ Health Equity Summit and further revised to reflect input from Summit attendees.Study DesignThis is a narrative review of the curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 332 publications
0
8
0
Order By: Relevance
“…21 A recent narrative review of implementation science and equity identified 4 principles that should guide implementation science to improve equity: (1) Racism must be recognized as a fundamental driver of inequities; (2) improved equity requires engagement of community members and other relevant partners; (3) equitable health care requires multisector partnerships; and (4) context is central to health care equity. 22 A key aspect of implementation science includes involving community partners early in the development and testing of interventions and including outcomes such as reach and representativeness of the intervention to ensure that a therapy does not have the unintended consequence of exacerbating disparities. Including community partners as investigators may enhance uptake and sustainability of the intervention through the insights they provide into population needs and adaptations required for longterm use.…”
Section: Defining Implementation Science and Relationship With Equitymentioning
confidence: 99%
“…21 A recent narrative review of implementation science and equity identified 4 principles that should guide implementation science to improve equity: (1) Racism must be recognized as a fundamental driver of inequities; (2) improved equity requires engagement of community members and other relevant partners; (3) equitable health care requires multisector partnerships; and (4) context is central to health care equity. 22 A key aspect of implementation science includes involving community partners early in the development and testing of interventions and including outcomes such as reach and representativeness of the intervention to ensure that a therapy does not have the unintended consequence of exacerbating disparities. Including community partners as investigators may enhance uptake and sustainability of the intervention through the insights they provide into population needs and adaptations required for longterm use.…”
Section: Defining Implementation Science and Relationship With Equitymentioning
confidence: 99%
“…Novel frameworks are needed to support translational dissemination in a manner that is equityoriented, or working to reduce the power imbalances represented by research participants, illness-oriented communities, historically marginalized groups, and/or geographic communities (Baumann et al, 2023). The clinical and translational science workforce represents individuals from a wide range of prior educational experiences and multidisciplinary background.…”
Section: Pedagogical Frameworkmentioning
confidence: 99%
“…[30][31][32][33] People who inject drugs face stigma and discrimination which shape their interactions with healthcare systems, and access to care.2,34, 35 Recent shifts towards equity-focused implementation science underscore the importance of acknowledging and addressing these unique challenges to enhance health outcomes for all. 30,[36][37][38] The use of an equityfocused theoretical lens can complement determinant frameworks such as the Theoretical Domains Framework (TDF) by providing a deeper understanding of how intersecting social identities and structural inequities in uence individuals' behaviors and attitudes, enriching the analysis of barriers and enablers to behavior change in healthcare settings.33,37,39,40 By considering the complex interplay of intersecting identities and structures of power within society (e.g., racism, classism, drug policy, stigmatization of HCV infection), an intersectionality lens has the potential to provide a more nuanced perspective on the factors in uencing the implementation of point-of-care HCV testing within needle and syringe programs. [41][42][43] Objective and research questions The HepCAST study aimed to use an intersectionality lens to explore the theory-informed barriers and enablers to point-of-care HCV antibody and RNA testing in a needle and syringe program in Montreal, Canada.…”
Section: Introductionmentioning
confidence: 99%